1978
DOI: 10.2134/agronj1978.00021962007000030028x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐statured Rice Response to Seeding and N Rates1

Abstract: Research on response of direct seeded rice (Oryza sativa L.) to interactions of seeding rate and N rate is very limited, although considerable work has been done in the tropical countries with transplanted rice. Understanding responses by U.S. rice cultivars to these factors is important not only for optimizing management, but also because it provides information concerning the need for further improvement of plant type. Therefore, our objective in this study was to determine what factors might limit performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
2
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 4 publications
9
43
2
2
Order By: Relevance
“…A negative relationship between panicle number per unit area and SPP has been widely reported (Matsushima, 1966;Wells and Faw, 1978;Jones and Snyder, 1987), and we also found that the average panicle number per unit area was higher at high and medium planting densities. In each cultivar, although the differences in D-SPP and SPP values among planting densities were not statistically significant, D-SPP and SPP tended to be larger at the low planting density than at the high planting density, and, in contrast, panicle number per unit area were smaller at the low planting density than at higher planting densities.…”
Section: Effects Of Planting Density On Average D-spp Sppsupporting
confidence: 82%
See 1 more Smart Citation
“…A negative relationship between panicle number per unit area and SPP has been widely reported (Matsushima, 1966;Wells and Faw, 1978;Jones and Snyder, 1987), and we also found that the average panicle number per unit area was higher at high and medium planting densities. In each cultivar, although the differences in D-SPP and SPP values among planting densities were not statistically significant, D-SPP and SPP tended to be larger at the low planting density than at the high planting density, and, in contrast, panicle number per unit area were smaller at the low planting density than at higher planting densities.…”
Section: Effects Of Planting Density On Average D-spp Sppsupporting
confidence: 82%
“…Shiratsuchi et al (2007) reported a strong positive relationship between SPP and tiller dry weight at heading, and Yao et al (2000) also showed the similar relationship in 32 cultivars. In addition, a negative relationship between panicle number and SPP has been widely reported (Matsushima, 1966;Wells and Faw, 1978;Jones and Snyder, 1987). Therefore, the difference in the numbers of tillers and panicles that results from different planting densities should also affect the SPP (Kuroda et al, 1999).…”
mentioning
confidence: 99%
“…Wells & Faw (1978) e Singh & Pillai (1996) têm atribuído o aumento do rendimento de grãos em decorrência do incremento da adubação nitrogenada ao aumento do número de grãos formados por panícula. No entanto, Ghobrial (1983) e Reddy et al (1986 também consideraram o aumento do número de panículas por unidade de área como um fator determinante do aumento do rendimento de grãos de arroz com incremento do nível de N aplicado.…”
Section: Resultsunclassified
“…Desta forma, no ano em que a resposta ao N foi menor, quando houve resposta, esta só ocorreu na densidade mais baixa de semeadura. Resultados semelhantes foram obtidos por Wells & Faw (1978).…”
Section: Resultsunclassified
“…The proportion of the latter may be increased by the larger and earlier productive tiller production, resulting in the increase in the degree of grain filling. Wells and Faw (1978) also concluded that excessive vegetative growth before anthesis limited grain yield under dense populations. Since the number of non-productive and weaker tillers were reduced by DW, the tillers received more light, accumulated more photosynthates to the panicles, and finally filled the grains more sufficiently under DW.…”
Section: Yield and Yield Componentsmentioning
confidence: 99%